Contractility of Induced Pluripotent Stem Cell-Cardiomyocytes With an MYH6 Head Domain Variant Associated With Hypoplastic Left Heart Syndrome - Kim, Min-Su; Fleres, Brandon; Lovett, Jerrell; Anfinson, Melissa; Samudrala, Sai Suma K.; Kelly, Lauren J.; Teigen, Laura E.; Cavanaugh, Matthew; Marquez, Maribel; Geurts, Aron M.; Lough, John W.; Mitchell, Michael E.; et al. (Frontiers in Cell and Developmental Biology, 2020)
Hypoplastic left heart syndrome (HLHS) is a clinically and anatomically severe form of congenital heart disease; however, its etiology remains largely unknown. We previously demonstrated that genetic variants in the MYH6 gene are significantly associated with HLHS. Additionally, induced pluripotent stem cell-derived cardiomyocytes (iPSC-CMs) from an HLHS-affected family trio (affected parent, unaffected parent, affected proband) carrying an MYH6-R443P head domain variant demonstrated dysmorphic sarcomere structure and increased compensatory MYH7 expression. Analysis of iPSC-CMs derived from the HLHS trio revealed that only beta myosin heavy chain expression was observed in CMs carrying the MYH6-R443P variant after differentiation day 15 (D15). Functional assessments performed between D20-D23 revealed that MYH6-R443P variant CMs contracted more slowly (40 ± 2 vs. 47 ± 2 contractions/min, P < 0.05), shortened less (5.6 ± 0.5 vs. 8.1 ± 0.7% of cell length, P < 0.05), and exhibited slower shortening rates (19.9 ± 1.7 vs. 28.1 ± 2.5 μm/s, P < 0.05) and relaxation rates (11.0 ± 0.9 vs. 19.7 ± 2.0 μm/s, P < 0.05). Treatment with isoproterenol had no effect on iPSC-CM mechanics. Using CRISPR/Cas9 gene editing technology, introduction of the R443P variant into the unaffected parent’s iPSCs recapitulated the phenotype of the proband’s iPSC-CMs, and conversely, correction of the R443P variant in the proband’s iPSCs rescued the cardiomyogenic differentiation, sarcomere organization, slower contraction (P < 0.05) and decreased velocity phenotypes (P < 0.0001). This is the first report to identify that cardiac tissues from HLHS patients with MYH6 variants can exhibit sarcomere disorganization in atrial but not ventricular tissues. This new discovery was not unexpected, since MYH6 is expressed predominantly in the postnatal atria in humans. These findings demonstrate the feasibility of employing patient-derived iPSC-CMs, in combination with patient cardiac tissues, to gain mechanistic insight into how genetic variants can lead to HLHS. Results from this study suggest that decreased contractility of CMs due to sarcomere disorganization in the atria may effect hemodynamic changes preventing development of a normal left ventricle.